2009
DOI: 10.1245/s10434-009-0858-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with False-Negative Sentinel Lymph Node Biopsy in Melanoma Patients

Abstract: This is the largest study to evaluate FN SLN results in melanoma, with a FN rate of 10.8%. FN results are associated with greater patient age, lower mean thickness, less frequent LVI, and greater risk of LITR. However, survival of patients with FN SLN is not statistically worse than that of patients with TP SLN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 33 publications
9
100
0
3
Order By: Relevance
“…11 Amongst other investigators, we have found comparable results in earlier studies: in line with other studies using this definition and an earlier report from our hospital the false-negative rate in the current study is 11%. 3,12 Remarkably, however, the false-negative rate recently dropped to 2% in our center. Recently data from the Sunbelt Melanoma Trial by Scoggins et al show no OS difference between patients with a false-negative SLN and patients with a true-positive SLN result.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 59%
See 1 more Smart Citation
“…11 Amongst other investigators, we have found comparable results in earlier studies: in line with other studies using this definition and an earlier report from our hospital the false-negative rate in the current study is 11%. 3,12 Remarkably, however, the false-negative rate recently dropped to 2% in our center. Recently data from the Sunbelt Melanoma Trial by Scoggins et al show no OS difference between patients with a false-negative SLN and patients with a true-positive SLN result.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 59%
“…Recently data from the Sunbelt Melanoma Trial by Scoggins et al show no OS difference between patients with a false-negative SLN and patients with a true-positive SLN result. 12 However, the authors discuss that their finding is also somewhat at odds with the MSLT, which showed that the survival of patients who developed clinically detected nodal metastases in de wide local excision-only group was worse than those who had nodal metastases detected by the SLNB.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…Neuschmelting, H.L., J.G., and M.F.K. have no conflicts of interest to the local nodal basin at the time of SLN excision (in-transit metastases) (6,(8)(9)(10)(11).…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous reports of the natural history after a positive sentinel node biopsy. 7,8,35,36,40,45,[50][51][52][53][54] In their meta-analysis, Mehrany and coworkers report a 66% disease-free survival rate after a positive sentinel lymph node biopsy. Over a median follow-up period of 10.5 months, the odds of recurrence were 19-fold greater in patients with a positive biopsy than in patients with a negative sentinel node biopsy (odds ratio 18.9, P ϭ 0.005).…”
Section: Positive Sentinel Lymph Node Biopsymentioning
confidence: 99%